The automatic transmission motorcycle ultrafine particles PM0.1 effects in the alveolar enlargement, depleted of septum alveolus, and lung inflammation - Arinto Yudi Ponco Wardoyo; Unggul Pujung Juswono; Johan A.E. Noor (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
Motorcycles smoke have been responsible inducing lungs related to diseases for a long time. This study was aimed to reveal the effect of the repeated exposure automatic transmission motorcycle smoke in the development of lungs damage in the wistar mice by observing the alveolar, the septum alveolar, and the tissues inflammation. Threes groups of the wistar mice had been labelled as control, C1, and C2 and keep in 30 x 20 x 20 cm3 chamber. The C1 group was introduced by the motorcycle smoke for 60 second and C2 for 100 seconds. The smoke was flowed into a chamber by using an air pump with the rate of 2 m/s. The smoke was exposed repeatedly to the mice as long as 10 sequence days, and the lung was observed for every 2 day. The alveolar size was observed by measuring the line core length. The septum alveolar was indicated by the depleted septum alveolus, and the inflammation was identified by the morphological way. All of the result were statistically analysed. The alveolar line core grew longer for the C1 and C2 group of 11±6 μm and 20±2 μm compared to the control. The Depleted Septum Alveolar increased up to 77% for the C1 group and 79% for the C2 group. The tissue inflammations were found in every sample. The R2 from statistical approach showed the strong correlation between the lung damage and the repeated exposures. The lung damage in terms of alveolar size enlargement, the increase of damage septum alveolus, and tissues inflammation were related to repeated exposure of motorcycle smoke.